Recurrent neurosarcoidosis: Two cases with different patterns of clinical and imaging presentation [Rekürren Nörosarkoidoz: Farklı Klinik ve Radyolojik Prezentasyonlar ile İki Olgu Sunumu] - (:unkn) unknown (Ege University Press, 2014)
Neuroarcoidosis can affect any part of the central and/or peripheral nervous system and in cases with neurological symptoms as their first manifestations, it is very challenging for the clinicians to make a differential diagnosis. Herein we report two different clinical presentations of neurosarcoidosis without an evidence of active systemic sarcoidosis. With our report, we would like to emphasize, particularly high rates of progression or recurrence of neurosarcoidosis with or without systemic involvement and requirements of early treatment and imaging follow-up. © 2014 Ege University Press. All rights reserved.
Keywords: Angiotensin converting enzyme; Diagnosis; Magnetic resonance imaging; Neurosarcoidosis